2015
DOI: 10.1063/1.4931354
|View full text |Cite
|
Sign up to set email alerts
|

Electric field controlled nanoscale contactless deposition using a nanofluidic scanning probe

Abstract: A technique for contactless liquid deposition on the nanoscale assisted by an electric field is presented. By the application of a voltage between the liquid inside a (FluidFM) nanofountain pen AFM probe and a substrate, accurate contactless deposition is achieved. This technique allows for the deposition of polar liquids on non-wetting substrates. Sodium sulfate dried deposits indicate that the spot size and height increases with t0.33±0.04 and t0.35±0.10, respectively. The minimum observed diameter was 70 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The SEM picture of the deposited structure morphology is shown in figure 3(c), with P = 60 mbar and E = −0.55 V. As shown in figure 3(a), the green curve represents the real-time position of the Z-axis probe, and the red curve denotes the real-time deflection of the AFP cantilever. Compared with the deflection information and the electrodeposition current of the simultaneous non-contact measurement probe [30], the measuring results obtained in this research were intuitive. More specifically, the deposition process can be directly reproduced by observing the green and red curves, and the deposition state can be effectively analyzed.…”
Section: Printing Rate and Structures Performance Analysismentioning
confidence: 86%
“…The SEM picture of the deposited structure morphology is shown in figure 3(c), with P = 60 mbar and E = −0.55 V. As shown in figure 3(a), the green curve represents the real-time position of the Z-axis probe, and the red curve denotes the real-time deflection of the AFP cantilever. Compared with the deflection information and the electrodeposition current of the simultaneous non-contact measurement probe [30], the measuring results obtained in this research were intuitive. More specifically, the deposition process can be directly reproduced by observing the green and red curves, and the deposition state can be effectively analyzed.…”
Section: Printing Rate and Structures Performance Analysismentioning
confidence: 86%
“…This would have a hugely detrimental impact on the patterning time, whereas the 3-4 mm s − 1 demonstrated in this paper compares favorably to the upper speeds of 10 mm s − 1 utilized in electron-beam lithography 36 . The use of emerging methods of EHD printing, such as combinations with AFM-capillaries for closed-loop nanoscale nozzle-surface separation 37,38 , would greatly improve the resolution we show here for continuous printing. This could be used to directly print far denser networks of nanoparticles, opening a route for the use of additive nanomanufacturing to create singleelectron device circuitry 5 , sensors 2 , and nanoplasmonic devices 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Such flow processes are very favorable for the fabrication or synthesis of nanomaterials with well‐defined sizes and geometries, highly ordered architectures, well‐regulated orientation, and desired unusual properties, which are difficult or impossible to achieve via the bulk or microscale processes. It is a promising and exciting direction of nanofluidics, where a few exploratory studies have been reported recently …”
Section: Nanofluidics For the Fabrication And Synthesis Of Nanomaterialsmentioning
confidence: 99%
“…Other interesting studies which have been reported in this direction may include the fabrication of nanoscale salt deposits, nanofibers, droplets, nano‐/microparticles, and polymeric conical structures by using nanofluidic flows. Although so far striking demonstrations are still lacking, much progress can be expected in the future.…”
Section: Nanofluidics For the Fabrication And Synthesis Of Nanomaterialsmentioning
confidence: 99%